Peningkatan Kemampuan Menulis Permulaan dengan Metode Analisis Glass - Khusna Yulinda Udhiyanasari; Nostalgianti Citra Prystiananta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the increase in the ability to write early using the glass analysis method. This research is a case study of grade 1 elementary school students who have difficulty writing beginning. After identification of the main factors children have difficulty writing (disgrafia), namely factors in their own children and the environment, especially parents and daily habits at home. The use of creative methods such as the glass analysis method, namely the separation of syllables, makes it easier for students to write because they remember one by one syllables that will be arranged into a word and sentence. Conclusion, the provision of learning using the glass analysis method can provide an improvement in the writing ability of students' beginning Keywords: Writing Ability, Glass Analysis Method